Continuous graphene fibers prepared by liquid crystal spinning as strain sensors for Monitoring Vital Signs. (September 2020) - Liu, Fuyao; Dong, Yubing; Shi, Ruike; Wang, Enliang; Ni, Qingqing; Fu, Yaqin
Graphical abstract: Abstract: Perfect graphene sheets are zero-gap semiconductors (semi-metals) with extremely high electron mobility and have considerable potential in electronics and optics, high sensitivity sensors, supercapacitors and biodevices. Practically applying the semiconductor properties of graphene has become the focus of research. We prepared a microscopically ordered graphene oxide fiber by liquid crystal spinning. The high concentration (50 mg ml −1 ) graphene oxide dispersion is favorable for forming highly ordered nematic phase in the spinning process. In a liquid crystal, graphene inside a fiber has an ordered regular structure arranged in parallel along the axial direction. High-strength (432.6 ± 12.7 MPa) and highly conductive (4.9 × 104 S/m) graphene fibers are obtained by chemical reduction, in which a strong π-π bonds forms between parallel graphene layers. Given that strain can change graphene band gap and affect electron transport, it is inherited to the graphene fiber, which is macroscopically conductive. Variations, strain response sensors made from this graphene fiber with high sensitivity, and strain range (2%–8%) can be used in the detection of body health signals (speech and pulse waves). These parameters have potential use in artificial electronics skin and wearable health detection.